Analyzing the effects of splitter blade on the performance characteristics for a high-speed centrifugal pump - Ye Yuan; Shouqi Yuan (Advances in Mechanical Engineering, 2017)
To add the splitter blades is an important technique to improve the pump performance characteristics. The effects of splitter blade on the pump performance and flow characteristics in a high-speed centrifugal pump were studied in this article. The numerical simulations were conducted to explore the steady and unsteady flows, and the simulation method was validated by the performance experiments on the full work conditions. The pump head was increased 10 m approximately, while the operating efficiency was raised nearly 4% by adding the splitter blades. The jet-wake structure in the outflow from the impeller was also improved obviously. The jetting flow increases greatly, and the flow separations in the blade passage are diminished. Moreover, the splitter blade obviously makes the turbulence kinetic energy distribution harmony and decreases the dissipation of turbulent kinetic energy to improve the flow stability. The pressure fluctuations in the frequency domain were proved to distribute more evenly in the complex impeller, which enhanced the steady flow in the pump.